Predictive and prognostic biomarkers for neoadjuvant chemoradiotherapy in locally advanced rectal cancer. Issue 1 (October 2015) - Lim, S.H.; Chua, W.; Henderson, C.; Ng, W.; Shin, J.-S.; Chantrill, L.; Asghari, R.; Lee, C.S.; Spring, K.J.; de Souza, P.
Highlights Biomarkers are needed to assess treatment response in locally advanced rectal cancer. Experimental markers include proteins involved in cell proliferation and apoptosis. There is no one biomarker currently that has robust clinical utility. Microarrays that can interrogate a tumour for multiple candidates have potential. Circulating tumour cells or nucleic acids are likely the way forward.